Effect of different soil water managements on the selectivity of fomesafen in conventional and RR soybean - Gonçalves, Clebson G.; Marques, Ricardo F. [UNESP]; de Marchi, Sidnei R.; Martins, Dagoberto [UNESP] (Taylor & Francis, 2022)
The study aimed to study the selectivity of the herbicide fomesafen, sprayed at different growth stages of the conventional and RR soybean cultivars, under different soil water managements. Two soybean cultivars were used: MG/BR 46 Conquista (conventional) and BRS Valiosa (RR), submitted to the spraying of fomesafen at two phenological stages (V2-first open trefoil; V4-third open trefoil), under three soil water conditions (-0.03, −0.07, and −0.5 MPa). Under water scarcity conditions, soybean plants have lower visual phytotoxicity when subjected to the spraying of the herbicide fomesafen. There were anatomical differences between the leaf blades of the conventional (MG/BR 46 Conquista) and transgenic (BRS Valiosa–RR) cultivars, and the water scarcity changed the anatomy of the soybean plants. The condition of moderate water shortage (-0.07 MPa) led the conventional cultivar to present a lower development than the transgenic cultivar. The transgenic cultivar had a greater ability to sustain the biological nitrogen fixation under moderate water shortage conditions (-0.07 MPa) than the conventional cultivar.
Keywords: Glycine max; morphology; phytotoxicity; symbiotic N2-fixing; water deficit.H